Heat and temperature experiment designs to support students' conception on nature of science - Eka Cahya Prima; Setiya Utari; Didi Teguh Chandra; Lilik Hasanah; Dadi Rusdiana (OmniaScience, 2018)
Constructing student's scientific literacy is still a challenge for the developing country. PISA 2015 report on scientific literacy showed that Indonesia was positioned at 62th out of 70 countries. According to this result, the students are only able to explain the simple science phenomenon because some learning activities have not followed good scientific inquiry as a fundamental aspect of the nature of science. To overcome the problem, PISA 2015 stated that teachers are suggested to design well-structured laboratory activities that make actual scientific concepts and ideas, and help students make the connection among the hands-on activities, scientific ideas and real-life problems. Moreover, the student's conception of the nature of scientific knowledge is required to help a student become a scientifically literate person. This work aims to construct science knowledge and contextual problems to support students' conception of the nature of science. In the case of the physics subject, eight new heat and temperature experiment designs are proposed to construct students' scientific literacy in high schools. The aspects of scientific literacy on experiment designs are developed based on PISA 2015 frameworks.